1989
DOI: 10.1111/j.1600-0447.1989.tb01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive‐compulsive symptoms in childhood and adolescence

Abstract: We investigated 61 patients (38 boys and 23 girls) under 18 years of age with obsessive-compulsive symptoms seen in the Department of Psychiatry, Nagoya University Hospital, from 1982 until 1986. In this period, a total of 1293 patients under 18 years of age visited the clinic. The percentage of patients with obsessive-compulsive symptoms was 5%. The earliest onset of symptoms was at age 3 years, and the average age of onset was 11.6 years. We found no particular tendency in terms of the number of siblings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 12 publications
5
22
1
3
Order By: Relevance
“…A preponderance of boys was found in the OCD group, which is also previously reported in some extensive studies of OCD in children and adolescents [15,17,19,28,29], Riddle et al [10], however, reported almost equal repre sentation of boys and girls.…”
Section: Discussionsupporting
confidence: 45%
“…A preponderance of boys was found in the OCD group, which is also previously reported in some extensive studies of OCD in children and adolescents [15,17,19,28,29], Riddle et al [10], however, reported almost equal repre sentation of boys and girls.…”
Section: Discussionsupporting
confidence: 45%
“…Zeitlin (1986) described symptomatology in a few adults who were admitted in both adulthood and childhood with OCD, and found that the consistency of symptoms was very high. The chnical picture seen in children and adults seem in many ways to be alike, although children seem to have less pure obsessions than adults (Honjo et al, 1989;Swedo et al, 1989;R.apoport, 1986;Khanna & Srinath, 1988), but to the author's knowledge no follow-up study has so far demonstrated the intra-individual phenomenological stability of obsessive-compulsive symptomatology.…”
Section: Introductionmentioning
confidence: 86%
“…The most recent epidemiological evaluations have reported an incidence ranging from 1 to 5%, but this reflects regional variations, from as little as 1% in the USA [7] to 1.3% in Denmark [8], 3.6% in Israel [9] and 5% in Japan [10]. The lastest data from the British nationwide survey of child mental health, carried out on a sample of more than 10,000 subjects, showed a lower prevalence of 0.25% [11], but, when subsyndromal forms were included, as it has been the case in another study [12], the prevalence increased significantly up to 12.0%.…”
Section: Epidemiologymentioning
confidence: 99%